La autoestima y su incidencia en el rendimiento escolar de los estudiantes de la escuela de EGB. Rosa Elena Eguiguren de la ciudad de Loja, periodo académico 2018- 2019. Lineamientos alternativos. - Escobar Chamba, Mercedes Abigail (2020)
The present research called “Self-Esteem and its impact on the school performance of the students of the Escuela de EGB. Rosa Elena Eguiguren of the city of Loja, academic period 2018-2019. Alternative guidelines has a general objective: is to determine the selfesteem and its impact on the school performance of the students of the EGB School and as specific objectives: to characterize the self-esteem and its impact on the student's school performance; identify students' school performance; propose alternative guidelines that strengthen self-esteem and contribute to the student's school performance. The type of study is descriptive; non-experimental design; observational, descriptive, inductive, deductive, hermeneutical, analytical, synthetic and statistical methods; the techniques; observation, survey; instruments: observation sheet, questionnaire; diagnostic procedures, theoretical foundation, alternative guidelines approach; It follows that students' self-esteem is not adequate, because if students distrust their abilities, performances and abilities to solve daily school activities, their school performance will be affected. 12 students, 8 parents and the teacher participated in the research work. It is concluded that the strengthening of children's self-esteem develops greater security in their educational activities and their school performance will improve.